2018
DOI: 10.15361/1984-5529.2018v46n3p257-263
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the mycelial growth and germination of Stromatinia cepivora by plant extracts and essential oils

Abstract: Stromatinia cepivora is one of the major pathogens of Allium species worldwide. Assuming that substances produced by plants may be used in the management of this pathogen, the effect of plant extracts and essential oils on the mycelial growth and germination of S. cepivora was assessed in this study. The fungus was grown on PDA medium with aqueous and ethanolic extracts (20 %, m:v) of mentrasto, rue, ginger, false saffron, garlic and citronella at the concentrations of 1 or 10 mL L -1 and the essential oils of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
2
Order By: Relevance
“…The extract obtained from the milling and immersion in water, prepared by Garcia et al (2016) at 30% concentration, inhibited 27.71% of the growth of Ss, a result lower than that observed here (70.41%). The aqueous extract of this plant inhibited 30 and 20% of growth of Sc at concentrations of 20 and 2%, according to Fuga et al (2018), a result lower than that observed in the present study, of 70.83%. Autoclaved lyophilized extract, together with the culture medium, provided a 70.6% inhibition of Vd, according to Oliva et al (1999).…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…The extract obtained from the milling and immersion in water, prepared by Garcia et al (2016) at 30% concentration, inhibited 27.71% of the growth of Ss, a result lower than that observed here (70.41%). The aqueous extract of this plant inhibited 30 and 20% of growth of Sc at concentrations of 20 and 2%, according to Fuga et al (2018), a result lower than that observed in the present study, of 70.83%. Autoclaved lyophilized extract, together with the culture medium, provided a 70.6% inhibition of Vd, according to Oliva et al (1999).…”
Section: Resultscontrasting
confidence: 85%
“…On the other hand, this plant in the 2000 (0.2%) and 2500 ppm (0.25%) concentrations inhibited 94.44% of the Fox mycelial growth (Sreenivasa et al, 2011). The aqueous extract of this plant inhibited 52% growth of Sc at a concentration of 20%, according to Fuga et al (2018), a result lower than that observed in the present study, of 100% inhibition. No citronella Ss and Vd inhibition data were accessed, although there was good fungal inhibition in the present study (72.22%).…”
Section: Resultscontrasting
confidence: 72%